Efektivitas Konseling Kelompok Pendekatan Analisis Transaksional Untuk Mengatasi Burnout pada Karyawan Ophar PT. Telkom Kancatel Ungaran - Ferdinand Hindiarto; Ouys Alkharani (Jurnal Ilmiah Aset, 2008)
The lack of ability to cope stress causes a human being locked in a situation that overwhelmingly deteriorating his physical / mental exhaustion. This endless condition occurred in the personnel of network-operators, therefore they gain tediousness in their employment. This research aims in finding out the effectiveness of group counseling on the basis of Transactional Analysis Approach, in dealing with job-burn out of OPHAR (daily operators) on Kancatel Ungaran. The hypothesis proposed is that the Transactional Analysis Group Counseling is effective in overcoming the job-burnout. The subject of this research are 11 emloyers of PT. Telkom Kancatel Ungaran. The statistical analysis occupied in this research in the Wilcoxon Non Parametric Technique. The outcome illustrates that there is an extremely significant result of the pre and post treatment burnout by the implementation of Transactional Analysis Group Counseling, presenting the Z= -2,394, p < 0,001. This indicates that the hypothesis is acceptable.